College Students' Perceptions of and Responses to Academic Dishonesty: An Investigation of Type of Honor Code, Institution Size, and Student–Faculty Ratio. Issue 4 (19th May 2018) - Tatum, Holly E.; Schwartz, Beth M.; Hageman, Megan C.; Koretke, Shelby L.
Abstract : College students ( n  = 928) from small, medium, and large institutions with either a modified or no honor code were presented with cheating scenarios and asked to rate how dishonest they perceived the behavior to be and the likelihood that they would report it. No main effects were found for institution size or type of honor code. Student–faculty ratio was not correlated with responses to the cheating scenarios. Students from modified honor code schools perceived more severe punishments for cheating and understood the reporting process better than students from non–honor code schools. Implications for modified honor code systems are discussed.